Validation of a Computerized Version of the Trait Subscale of the Physical Appearance State and Trait Anxiety Scale in Mexican Preadolescents - Juan Francisco Aguirre; Yunuen Socorro Rangel-Ledezma; Perla Jannet Jurado-García; Humberto Blanco; Martha Ornelas; Carolina Jiménez-Lira; José René Blanco; Susana Ivonne Aguirre (MDPI AG, 2022)
Anxiety is a feeling of fear, dread or restlessness and can develop into a weight-related disorder. The objective was to analyze the psychometric properties of the trait anxiety subscale of the Physical Appearance State and Trait Anxiety Scale (PASTAS), as well as the invariance in Mexican preadolescents. The sample consisted of 604 participants, 285 female and 319 male, whose ages ranged between 11 and 12 years (M = 11.37; SD = 0.48). The questionnaire's factor structure was analyzed using confirmatory factor analyses. The analyses show the viability and adequacy of a two-factor structure (weight and non-weight factors) both for the total sample and for the populations of male and female. The two-factor structure showed adequate reliability and validity fit indicators. The factor structure, the factor loadings and intercepts are considered invariant according to the variable sex; however, differences between female and male participants were found for levels of anxiety caused by physical appearance. In conclusion, the PASTAS can be considered a convenient instrument to assess the variables related to anxiety generated by one's physical appearance, as well as allowing more participants to be quickly assessed.